(untitled) (Revista Contexto & Educação, 2023)
This essay assumes the Snapchat camera application as an allegory or figure of thought appropriate to characterize our time and, indeed, our relationship with time. From a conceptual study, inspired by Contemporary Sociological Theory, he examines the condition of heritage education in the “Snapchat era”. The argument presented seeks to address mainly two issues. How to think of cultural heritage when cultural contents are self-destructive? How to educate for the valuation of assets when the images produced last only 24 hours? From the analysis, it was found that in societies where individualization is in effect, there is a decline in organized collective memories; the expansion of museums and private collections, with no clear public purpose; the musealization of private collections and the decline of their national or integrating meanings. In the specific case of social actions that promote heritage guidelines, among them, heritage education tends to be in place for individualization or personalization of memories and cultural heritage.